Analysis of a training mesocycle and positional quantification in elite European soccer players - Owen, A. L.; Lago-Peñas, C.; Gómez, M.-A.; Mendes, B.; Dellal, A. (International Journal of Sports Science & Coaching, 2017)
Ensuring adequate levels of training and recovery at the elite level of professional soccer to maximise player performance has continued to drive the necessity to monitor the training load and physical training output of soccer players. The aim of this investigation was to analyse a training mesocycle whilst quantifying positional demands imposed on elite European soccer players. Sixteen players were assessed using global positioning systems and ratings of perceived exertion over a competitive training six-week mesocycle period. The positional demands and training loads were analysed in addition to match conditions (match location, match score) and player's age. Results from the investigation revealed that typical daily training loads (i.e. total distance, high-intensity distance, sprint distance, average speed, ratings of perceived exertion) did not differ throughout each week of the mesocycle in-season period. Further analysis revealed training loads were significantly lower on match day-1 when compared to training loads on match day-2, match day-3 and match day-4 preceding a match (p<0.05). Significant differences in physical outputs were also found between match day-2, match day-3 and match day-4 highlighting a structured periodised tapered approach (p<0.05). Lower average speeds were reported in training post-successful matches compared to defeats (p<0.05), and more specifically when a match was played away compared to home fixtures (p<0.05). To conclude, practitioners can maintain a uniformed and structured training load mesocycle whilst inducing variation of the physical outputs during the microcycle phase. Additionally, the investigation also provides a tapering approach that may induce significant variation of the positional demands. ABSTRACT FROM AUTHOR